Teaching Vector Architectures Using a MIPS Instruction Simulator - Alves, Fredy A. M.; Almeida, Danilo; Bragança, Lucas; Gomes, André B. M.; Ferreira, Ricardo S.; Nacif, José Augusto M. (International Journal of Computer Architecture Education, 2015)
Vector processors, along with the MIPS processor, constitute two important milestones in the development and teaching of computer architecture. In recent decades, several extensions of the MIPS instruction set have been specified, including a SIMD extension in 2014. This article presents the first vector simulator based on MIPS to be used in computer architecture classes in Computer Science and Engineering courses. The proposed implementation is based on MARS, an open-source MIPS32 simulator. The proposed simulator is called Vector MARS or VMARS and features a robust and intuitive interface that assists in the simulation of MIPS vector instructions while also supporting the standard MIPS32 instruction set. Along with the VMARS simulator, examples are provided to illustrate the use of vector instructions available in the MIPS extension.